Land Surface Temperature and its Relationship to Population Density - Mita Apriana; Erliza Syahrani (Journal of Applied Geospatial Information, 2022)
Population density due to urbanization contributes to the SUHI phenomenon and urban climate change. Understanding the SUHI phenomenon that brings enormous negative impacts to the environment and human life, Land Surface Temperature (LST) assessment is essential for creating a feasible and livable city. By utilizing the data of 1999 and 2018, this study aims to assess the LST value and its relationship to population density in Tanjungpinang city over two decades. As an island, Tanjungpinang has a vulnerability to SUHI and the climate change phenomenon. This study applied GIS and remote sensing models based on the mathematical formula of digital remote sensing images to calculate the LST value, and the relationship between LST and population density was examined using correlation analyses with Microsoft Excel. The results showed that Tanjungpinang city had increased 3.5oC in LST and 94.80% in density population over two decades. SUHI phenomenon has occurred during this period. It also indicated that there was a significant relationship between population density and LST. The LST spatial pattern spread from west to east of Tanjungpinang city was in line with the population density distribution pattern. The area with the highest percentage of population density addition and experienced the highest LST was Tanjungpinang Barat District. This study considers local governments to create effective population control and adaptive planning strategies for SUHI phenomenon mitigation.